Merekonstruksi Ibadah Kreatif: Sebuah Upaya Membangun Minat Remaja Kristen Untuk Bergereja - Novita, Diana; Setiawan, David Eko; Dean, Melania; -, Fariasa; Marcos, Carles Roberto (Kharisma: Jurnal Ilmiah Teologi, 2021)
This article aims to explore the church's efforts to rebuild creative worship so that it can attract Christian youth to come to worship. This is because Worship is no longer attractive, especially among Christian youth. Surver Bilangan Research Center (BRC) proved that as many as 28.2% said that there were many interesting activities outside the church, which made Christian youth less active in attending church due to boring worship, monotonous worship, lack of creativity, and the church did not have a good impact on Christian youth growth. The method used is literature study (document), which is data collection juxtaposed to build the church's understanding of reconstructing creative worship. Thus, the church needs to reconstruct creative worship in order to attract the attention and interest of Christian youth to come to worship. As a result, Christian youth can be active in church by planning a worship program that is not boring, making simple decorations, holding worship activities interspersed with outdoor activities, fellowships together after worship. Artikel ini bertujuan untuk menggali upaya gereja untuk membangun kembali ibadah kreatif sehingga dapat menarik minat remaja Kristen untuk datang beribadah. Hal ini di karenakan Ibadah saat ini sudah tidak menarik khususnya dikalangan remaja Kristen. Surver Bilangan Research Center (BRC) membuktikan bahwa sebanyak 28,2% mengatakan bahwa ada banyak kegiatan yang menarik diluar gereja sehingga membuat remaja Kristen kurang aktif bergereja dikarenakan Ibadah yang membosankan, ibadah yang monoton, kurang kreatif, dan gereja tidak memberi dampak yang baik bagi pertumbuhan remaja Kristen. Metode yang digunakan adalah studi literatur (dokumen), yaitu pengambilan data yang disandingkan untuk membangun pemahaman gereja mengenai merekonstruksi ibadah kreatif dengan demikian gereja perlu melakukan rekonstruksi ibadah kreatif guna menarik perhatian dan minat remaja Kristen untuk datang beribadah. Hasilnya remaja Kristen dapat aktif bergereja dengan merencanakan program ibadah yang tidak membosankan, membuat dekorasi sederhana, mengadakan kegiatan ibadah diselingi dengan kegiatan outdoor, fellowship bersama-sama setelah ibadah.